1982
DOI: 10.1079/bjn19820130
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of high- and low-methoxyl pectins on blood and faecal lipids in man

Abstract: 1, The effects on blood and faecal lipids of the addition of 15 g of either high-or low-methoxyl pectin to the habitual diets of ten healthy young adults have been studied.2. Serum total cholesterol levels were reduced by a mean of 16% during consumption of low-methoxyl pectin and 18% during consumption of high-methoxyl pectin. High density lipoprotein cholesterol levels and triglyceride levels were unchanged.3. There was no difference in faecal fat and steroid excretion between the two pectins. 4.The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
3

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 23 publications
1
35
1
3
Order By: Relevance
“…Citrus pectin sources (high DM and high MW) exerted greater LDL cholesterol-lowering properties than low DM and low MW of citrus pectin and high DM of orange pulp fiber [29]. However, Judd and Truswell [30] reported that LMP has similar cholesterol-lowering effects compared to HMP. Wet and dry weights of feces were higher on HMP, while gut transit time and fecal water were similar in both groups (HMP and LMP).…”
Section: Characteristic Of Samplesmentioning
confidence: 92%
“…Citrus pectin sources (high DM and high MW) exerted greater LDL cholesterol-lowering properties than low DM and low MW of citrus pectin and high DM of orange pulp fiber [29]. However, Judd and Truswell [30] reported that LMP has similar cholesterol-lowering effects compared to HMP. Wet and dry weights of feces were higher on HMP, while gut transit time and fecal water were similar in both groups (HMP and LMP).…”
Section: Characteristic Of Samplesmentioning
confidence: 92%
“…Alguns mecanismos são propostos para explicar a ação das fibras solúveis na redução dos níveis de colesterol sérico e um deles é baseado na propriedade das fibras solúveis em hidratar-se no meio aquoso do intestino delgado, formando géis caracterizados por ligações cruzadas com os sais biliares, reduzindo o colesterol sérico, uma vez que o colesterol é usado para o reabastecimento de sais biliares no organismo (Judd & Truswell, 1982;Eastwood, 1992;Melo et al, 2007).…”
Section: (Recebido Em 12 De Setembro De 2008 E Aprovado Em 12 De Janeunclassified
“…Oat gum and Guar gum were slightly less effective and decreased serum cholesterol by approximately 22%, compared with values for cellulose-fed rats. Pectin has been reported to have a wide range of effects, depending on molecular weight and degree of methoxylation (Ebihara et al 1979;Judd and Truswell 1982), whereas oat bran and soy fibre produce modest effects (Anderson et al 1994;Anderson 1995). In humans, psyllium and guar gum are reported to be the most effective cholesterol-lowering soluble fibres (Anderson et al 1990).…”
Section: Role Of Dietary Fibre In Prevention Of Cardiovascular Diseasementioning
confidence: 99%